Intcal09 and Marine09 Radiocarbon Age Calibration Curves, 0-50,000 Years Cal Bp Rid F-4952-2011 Rid B-7298-2008 - Reimer, P. J.; Baillie, M. G. L.; Bard, E.; Bayliss, A.; Beck, J. W.; Blackwell, P. G.; Ramsey, C. Bronk; Buck, C. E.; Burr, G. S.; Edwards, R. L.; Friedrich, M.; Grootes, P. M.; et al. (Radiocarbon, 2009)
The IntCal04 and Marine04 radiocarbon calibration curves have been updated from 12 cal kBP (cal kBP is here defined as thousands of calibrated years before AD 1950), and extended to 50 cal kBP, utilizing newly available data sets that meet the IntCal Working Group criteria for pristine corals and other carbonates and for quantification of uncertainty in both the (14)C and calendar timescales as established in 2002. No change was made to the curves from 0-12 cal kBP. The curves were constructed using a Markov chain Monte Carlo (MCMC) implementation of the random walk model used for IntCal04 and Marine04. The new curves were ratified at the 20th International Radiocarbon Conference in June 2009 and; ire available in the Supplemental Material at www.radiocarbon.org.
id: 1983; PT: J; UT: WOS:000274407500002

Radiocarbon age of late glacial deep water from the equatorial Pacific - Broecker, W.; Clark, E.; Barker, S.; Hajdas, I.; Bonani, G.; Moreno, E. (Paleoceanography, 2007)
Radiocarbon age differences for pairs of coexisting late glacial age benthic and planktic foraminifera shells handpicked from 10 sediment samples from a core from a depth of 2.8 km in the western equatorial Pacific are not significantly different from that of 1600 years calculated from measurements on prenuclear seawater. This places a lower limit on the depth of the interface for the hypothetical radiocarbon-depleted glacial age seawater reservoir required to explain the 190% drop in the (14)C/C for atmospheric CO(2), which occurred during the mystery interval (17.5 to 14.5 calendar years ago). These measurements restrict the volume of this reservoir to be no more than 35% that of the ocean. Further, (14)C measurements on a single Last Glacial Maximum age sample from a central equatorial Pacific core from a depth of 4.4 km water fail to reveal evidence for the required 5- to 7-kyr age difference between benthic and planktic foraminifera shells if the isolated reservoir occupied only one third of the ocean. Nor does the (13)C record for benthic forams from this abyssal core yield any evidence for the excess respiration CO(2) expected to be produced during thousands of years of isolation. Nor, as indicated by the presence of benthic foraminifera, was the dissolved oxygen used up in this abyssal water.
id: 413; 165MC Times Cited:10 Cited References Count:18

Anomalous radiocarbon ages for foraminifera shells - Broecker, W.; Barker, S.; Clark, E.; Hajdas, I.; Bonani, G. (Paleoceanography, 2006)
The causes for discordant radiocarbon results on multiple species of planktonic foraminifera from high-sedimentation-rate marine sediments are investigated. We have documented two causes for these anomalous results. One is the addition of secondary radiocarbon for which we have, to date, only one firm example. It involves an opal-rich sediment. The other is the incorporation of reworked material. Again, we have, to date, only one firm example. It involves a rapidly deposited ocean margin sediment. However, we have three other examples where reworking is the most likely explanation. On the basis of this study it is our conclusion that, where precise radiocarbon dating of high-deposition-rate marine sediment is required, a prerequisite is to demonstrate that concordant ages can be obtained on pairs of fragile and robust planktic shells. For sediment rich in opal, it is advisable to check for secondary calcite by comparing ages obtained on acid-leached samples with those on unleached samples.
id: 980; 041JB Times Cited:7 Cited References Count:7

Ventilation of the glacial deep Pacific Ocean - Broecker, W.; Barker, S.; Clark, E.; Hajdas, I.; Bonani, G.; Stott, L. (Science, 2004)
Measurements of the age difference between coexisting benthic and planktic foraminifera from western equatorial Pacific deep-sea cores suggest that during peak glacial time the radiocarbon age of water at 2-kilometers depth was no greater than that of today. These results make unlikely suggestions that a slowdown in deep-ocean ventilation was responsible for a sizable fraction of the increase of the ratio of carbon-14 (14C) to carbon in the atmosphere and surface ocean during glacial time. Comparison of 14C ages for coexisting wood and planktic foraminifera from the same site suggests that the atmosphere to surface ocean 14C to C ratio difference was not substantially different from today's.
Broecker, WallaceBarker, StephenClark, ElizabethHajdas, IrkaBonani, GeorgesStott, Lowelleng2004/11/13 09:00Science. 2004 Nov 12;306(5699):1169-72.

Persistent solar influence on North Atlantic climate during the Holocene - Bond, G.; Kromer, B.; Beer, J.; Muscheler, R.; Evans, M. N.; Showers, W.; Hoffmann, S.; Lotti-Bond, R.; Hajdas, I.; Bonani, G. (Science, 2001)
Surface winds and surface ocean hydrography in the subpolar North Atlantic appear to have been influenced by variations in solar output through the entire Holocene. The evidence comes from a close correlation between inferred changes in production rates of the cosmogenic nuclides carbon-14 and beryllium-10 and centennial to millennial time scale changes in proxies of drift ice measured in deep-sea sediment cores. A solar forcing mechanism therefore may underlie at least the Holocene segment of the North Atlantic's "1500-year" cycle. The surface hydrographic changes may have affected production of North Atlantic Deep Water, potentially providing an additional mechanism for amplifying the solar signals and transmitting them globally.
id: 1397; Bond, G Kromer, B Beer, J Muscheler, R Evans, M N Showers, W Hoffmann, S Lotti-Bond, R Hajdas, I Bonani, G New York, N.Y. Science. 2001 Dec 7;294(5549):2130-6. Epub 2001 Nov 15.

The North Atlantic's 1-2 kyr climate rhythm: Relation to Heinrich events, Dansgaard/Oeschger cycles and the Little Ice Age (Book Section) - Bond, G. C.; Showers, W.; Elliot, M.; Evans, M.; Lotti, R.; Hajdas, I.; Bonani, G.; Johnson, S. (Mechanisms of global climate change at mellennial time scales, 1999)
id: 216